Pengaruh Musik terhadap Peforma Sapi Perah FH Laktasi - Widjaja, Nilawati; Mutiasari, Dina Nur; Akhdiat, Tedi; Permana, Hilman (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2018)
This research aimed to analyze the effect of music to feed consumption, milk production, and feed conversion in milk cows FH in lactation period. This research was experimental study using Complete Randomized Design (CRD) with 4 treatments consisted in M0 (without hearing music), M1 (hearing traditional music), M2 (hearing jazz music), and M3 (hearing classical music). Each treatments was replicated 5 times. Observed variables namely feed consumption, milk production, and feed conversion. Data were analyzed using variance, if there is a significant difference in treatments effects, it will be followed by Duncan’s Multiple Test Area. Based on the results and discussion, there are two kinds of conclusions can be drawn as follows music contributes effects to the performance of milk cows FH in lactation period, classical music contributes the optimal performance of milk cows FH in lactation period.